(untitled) (Bangladesh Journal of Botany, 2025)
In this study, the seedlings of Actinidia arguta were used as the experimental materials. Arbuscular mycorrhizal fungi (AMF), Rhizophagus irregularis, and the canker pathogen Dothiorella gregaria were inoculated. The effects of AMF on the biomass of roots, stems and leaves of Actinidia arguta, the contents of malondialdehyde (MDA), proline, and stem cellulose, as well as the activities of disease-resistant enzymes such as superoxide dismutase (SOD), catalase (CAT), polyphenol oxidase (PPO), chitinase, and polygalacturonase were determined. The results showed that the inoculation of AMF could increase the biomass of roots and stems of Actinidia arguta to enhance the tree vigor and reduce the incidence of canker disease. The inoculation of AMF could significantly reduce the MDA content in the stems and roots of Actinidia arguta infected with the disease, increase the proline content in the leaves and roots, and improve the PPO activity in roots, stems and leaves, the SOD activity in stems, and the CAT activity in leaves. In the early stage of AMF inoculation, the activities of chitinase and β-1,3-glucanase in stems and roots could be increased. It is concluded that AMF enhances the resistance of Actinidia arguta to canker disease and its disease resistance by accumulating proline, reducing the MDA content, and increasing the activities of SOD, CAT, and PPO. Bangladesh J. Bot. 54(3): 695-702, 2025 (September) Special